The Italian Approach to Fighting Organised Crime - Bulatović, Aleksandra (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
Modern organized crime is a highly dynamic phenomenon that challenges social control policy in various ways. Curbing organized crime is fundamentally connected to regulatory mechanisms whose effectiveness predominantly depends on institutional coordination. In Italy this is especially pronounced, as there is a historical continuity between the Mafia and the country’s political elite, while the aspirations of the Mafia to influence public governance are a traditional feature of Italian organized crime. Such a strategy by organized crime targets institutions and seeks to corrupt, co-opt or threaten them into cooperation. This explains why Italian anti-Mafia strategy rests on a quest to transform institutional structures so as to make them both more resilient to co-option by organized crime and more effective in aggressively fighting the Mafia. The strategy thus includes the establishment of various specialized institutions, which are highly autonomous in their operation on the one hand, with constant improvements in the coordination of all other, more traditionally "systemic" control agencies, such as the police force and the prosecution. Despite some impressive results achieved in Italy through this approach, activities of the Mafia continue at high intensity. The most recent Anti-Mafia strategic trends are critically evaluated in this text, which adopts a phenomenological conceptualization of organized crime.